ANALYSIS OF FACTORS AFFECTING STUDENTS’ LOW SPEAKING ABILITY OF TENTH GRADE STUDENTS AT SMAN 5 SUMATERA BARAT - Jingga Wulandari; Dodi Widia Nanda; Martiya Nurni Khairita (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
This study aims to analyze the internal and external factors causing the low speaking ability of tenth-grade students at SMAN 5 Sumatera Barat, whores scores fell below the Minimum Mastery Criterion (KKM) of 75. This research employed a qualitative descriptive design to investigate the phenomenon deeply. Data were collected through non-participant classroom observations, open-ended questionnaires and semi-structured interviews with one English teacher and three selected students. The data were analyzed using Braun & Clarke’s thematic analysis framework systematically. The findings identified 36 conceptual codes revealing that students face linguistic deficits, namely limited vocabulary and pronunciation difficulties, which trigger psychological distress including high speaking anxiety, low self-confidence and low learning motivation. Meanwhile, the external factors showed that these individual barriers are worsened by monotonous teaching strategies, an unsupportive classroom environment dominated by a toxic roasting culture among peers, limited practice opportunities, intrusive teacher feedback and inadequate learning facilities. In conclusion, the complex interaction between these linguistic-affective barriers and a restrictive classroom ecosystem forces students to execute defensive behaviors, such as speaking in whispers, reverting to local dialects or resorting to absolute silence, which ultimately paralyzes their English communicative competence.